“They didn’t break me either way”. Women, Captivity and Interrogation in World War II: Resurfacing Self-Empowering Narratives - Simona Tobia (Revue LISA)
Interrogation and questioning are often remembered as life-changing by those who have been incarcerated in wartime, and they represent a key element of the prisoner of war experience in memories and personal narratives of former captives. However, women’s accounts of interrogation and questioning in World War II are not as easy to find as men’s. Women only rarely fit the definition of POW because even when they were combatants, they hardly were legally so. Perhaps more importantly, female prisoners have not entered the collective memory as strongly as male prisoners, and it is essential to resurface women’s empowering personal accounts and life stories of these experiences in American archives and museums. The in-depth secondary analysis of oral history narratives held at the sound archives of the Veterans History Project within the Library of Congress, and at the United States Holocaust Memorial Museum, in Washington, DC, provides a series of case-studies to show how narrators were affected by their experiences of incarceration and to what extent their gendered memories fit within the shared memories of captivity in wartime. The article concludes that the way these women came to terms with their violent past challenges ideas about the vulnerability of women in captivity and that their narratives reach surprisingly empowering epilogues.